Leadership Styles of Madrasah Principals Towards Sustainable Education: A Systematic Review - Widiastuti; Rosita Endang Kusmaryani (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
In this modern era, the role of madrasah principals is not only limited to being administrators but also as leaders who are able to bring positive changes in Islamic education. In the context of sustainable education, the leadership style applied by madrasah principals has a crucial role in shaping an inclusive and progressive organisational culture. Therefore, research on the various leadership styles of madrasah principals is important in supporting efforts towards sustainable and quality Islamic education. This type of research is descriptive qualitative. The research technique used in this research is documentary research, based on literature data from several books and journals related to leadership communication in education. It can be concluded that the leadership style applied by the madrasah head has a significant impact on efforts to achieve sustainable Islamic education. Various leadership styles, such as authoritarian, democratic, transformational and transactional, influence organisational culture, staff motivation and the quality of student learning. Madrasah principals need to adopt leadership styles that are adaptive and responsive to the dynamics of change, as well as integrate Islamic values in madrasah management to contribute positively to building a sustainable and quality Islamic education in the future. Thus, research and development in the context of the leadership style of madrasah principals is essential in facing the challenges and opportunities in developing relevant, inclusive Islamic education that is relevant, inclusive and sustainable for future generations.